167PPrognostic impact of the C-reactive protein/albumin ratio in advanced pancreatic cancer treated with GEM plus nab-PTX or FOLFIRINOX: Based on the results of a multicenter retrospective study (the NAPOLEON study). (24th November 2019) - Makiyama, A; Nakazawa, J; Otsuka, T; Shimokawa, M; Koga, F; Ueda, Y; Komori, A; Arima, S; Fukahori, M; Honda, T; Shibuki, T; Shirakawa, T; et al.
Abstract: Background: GEM plus nab-PTX (GnP) and FOLFIRINOX (FFX) have been shown to improve overall survival for advanced pancreatic cancer patients. However, clinical utility of C-reactive protein/albumin ratio (CAR) as prognostic factor for the patients treated with GnP or FFX remains unclear. We conducted the exploratory analysis to elucidate prognostic impact of CAR using a multicenter retrospective study (the NAPOLEON study) cohort which examined the efficacy and safety of GnP and FFX in clinical practice. Methods: Between December 2013 to March 2017, 255 patients with unresectable advanced or recurrent pancreatic cancer who received GnP or FFX as 1st-line chemotherapy at 14 centers participating in the NAPOLEON study were examined. Patient characteristics at the start of 1st and 2nd line chemotherapy including age, gender, ECOG performance status, primary tumor site, disease status, metastatic site, underwent biliary drainage or not, treatment regimen at 1st line chemotherapy, LDH and CAR were analyzed to investigate correlation with prognosis by Cox regression model. The cut-off value of CAR adopted 0.54 based on a previous study. Patients were divided into groups according to CAR level less than 0.54 (CAR-low) and 0.54 or greater (CAR-high). Results: Cox regression analysis of OS identified underwent biliary drainage (HR: 1.76, 95%CI: 1.19–2.61), CAR-high (HR: 1.52, 95%CI: 1.05–2.21), and higher LDH level (HR: 2.10, 95%CI: 1.36–3.22) as significant factors at the start of 1st-line chemotherapy. Similarly, Cox regression analysis of OS identified a poor PS (HR: 1.62, 95%CI: 1.07–2.47), a high level of CA19-9 (HR: 2.14, 95%CI: 1.07–4.29) and CAR-high (HR: 2.15, 95%CI: 1.32–3.49) as significant factors at the start of 2nd-line chemotherapy. Eighty-six of 140 patients (82.7%) with CAR-high at the start of 1st-line chemotherapy still remained CAR-high at the start of 2nd-line chemotherapy. Conclusions: CAR may be useful prognostic factor at the start of both 1st and 2nd-line treatment. Almost all the patients with CAR-high before 1st line treatment still remained CAR-high after 1st line treatment. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.